TÁLIM ISKERLIGINDE OQITIW METODLARIN KLASSIFIKACIYALAW - Saytbekova, S.; Muratbaev, J. (SCIENCE and SOCIETY, 2022)
This article discusses the entire palette of methods of educational activity in the most formalized way, so that the choice of methods can be carried out for the given goals, its own typology is proposed, which has a clear classification feature - the openness of the elements of the educational process for the student.